How Well Do Institutional Theories Explain Firms’ Perceptions of Property Rights? - Ayyagari, Meghana; Demirgüç-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2012)
The authors examine how well several institutional and firm-level factors and their interactions explain firms' perceptions of property rights protection. Their sample includes private and public firms that vary in size from very small to large in 62 countries. Together, the institutional theories they investigate account for approximately 70 percent of the country-level variation, indicating that the literature is addressing first-order factors. Firm-level characteristics such as legal organization and ownership structure are comparable to institutional factors in explaining variation in property rights protection. A country's legal origin and formalism index predict property rights variation better than its openness to international trade, its religion, its ethnic diversity, natural endowments or its political system. However, these results are driven by the inclusion of former socialist economies in the sample. When the authors exclude the former socialist economies, legal origin explains considerably less than openness to trade and endowments. Examining a broader set of variables for robustness, they again find that when they exclude former socialist countries, legal origin explains comparatively little of the variation in perceptions of judicial efficiency, corruption, taxes and regulation, street crime, and financing.